The Effect of Differentiated Instruction in Teaching English Language for Second Intermediate Class Students - Abbas, Alyaa Ali (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The study explores the effect of Differentiated Instruction (DI) on English language skills for second intermediate class students. DI is an instructional approach that modulates instruction to accommodate students' varying readiness levels, interests, and learning profiles by modifying content, process, and product. A quasi-experimental method was used that involved two groups: an experimental group taught using DI strategies and a control group taught using traditional methods. The sample included 70 students of a secondary school in Baghdad. Data were collected using pre- and post-tests to measure English language achievement and through a questionnaire to identify students' attitudes toward the learning process. Results were found to reflect statistically significant progress in the experiment group compared to the control group (p < 0.01). Additionally, students under DI exhibited more engagement and motivation. These results prove the effectiveness of DI to enhance English language learning performance in EFL contexts.